2015
DOI: 10.1186/s12886-015-0058-3
|View full text |Cite
|
Sign up to set email alerts
|

The course of dry eye after phacoemulsification surgery

Abstract: BackgroundThe aim of this retrospective study was to evaluate the course of dry eye syndrome after phacoemulsification surgery.MethodsOne hundred and ninety-two eyes of 96 patients (30 males, 66 females) with chronic dry eye syndrome and cataract, who had undergone phacoemulsification surgery were enrolled in this study.ResultsTheir mean age was 68.46 ± 8.14 standard deviation (SD) (range 56–83) years . Thirty of them (31 %) were males and 66 (69 %) were females. Ocular Surface Disease Index (OSDI) questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
66
2
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 22 publications
15
66
2
8
Order By: Relevance
“…Phacoemulsification surgery may aggravate the signs and symptoms of dry eye and affect dry eye test values in chronic dry eye patients in short term. However, in the long term, signs and symptoms of dry eye decrease and dry eye test values return to preoperative values (Cetinkaya et al, ). It may be that this complaint should not be considered a complication.…”
Section: Discussionmentioning
confidence: 99%
“…Phacoemulsification surgery may aggravate the signs and symptoms of dry eye and affect dry eye test values in chronic dry eye patients in short term. However, in the long term, signs and symptoms of dry eye decrease and dry eye test values return to preoperative values (Cetinkaya et al, ). It may be that this complaint should not be considered a complication.…”
Section: Discussionmentioning
confidence: 99%
“…ФЭ, как и многие оперативные вмешатель-ства, связанные с травмой роговицы и дли-тельной послеоперационной противовоспали-тельной терапией, дестабилизирует слёзную плёнку, что может приводить к появлению или усугублению проявлений синдрома сухого глаза [5,6,18].…”
Section: Discussionunclassified
“…Полученные данные показали зна-чительное снижение слезопродукции и времени разрыва слёзной плёнки, увеличение выражен-ности складок конъюнктивы, усиление прокра-шивания конъюнктивы витальными красителями и субъективных жалоб пациентов [2]. Эти явле-ния также могут усугубляться после ФЭ [5,6,18], что стало причиной досконального изучения морфологических изменений эпителия роговицы в послеоперационном периоде по данным конфо-кальной микроскопии in vivo.…”
Section: Introductionunclassified
“…This contrasts with other studies which have reported a higher prevalence of the dry eye in females than in males in the general population. 14,15 An association of dry eyes with postmenopausal females is well known. The results in our study may have been influenced by a larger number of males undergoing SICS as compared to females.…”
Section: Discussionmentioning
confidence: 99%